Strategic Autonomy for ROK: Intellectual Pipe Dream or Political Reality? - K. V. Asmolov; A. V. Soloviev (Международная аналитика)
The discourse of “strategic autonomy,” which has gained popularity in the Republic of Korea in recent years, has yet to undergo serious theoretical revision. This article attempts to ﬁll the gap by examining the South Korean discourse of “middle powers,” from which the discourse of “strategic autonomy” grew, and the socio-historical analysis of Korean perceptions of political subjectivity, which developed under the powerful inﬂuence of both Western ideas from the early 20th century and the political realities of the military alliance with the United States. In the ﬁrst section the authors examine the speciﬁcs of South Korea’s use of the concept of “strategic autonomy” in relation to its foreign policy strategy. This concept is examined using a constructivist paradigm. In the second section, the authors examine the discourse of “middle power,” around which the concept of “strategic autonomy” is built. Compared to the former, this concept is quite elaborated in Western and Korean political discourses. Finally, the third section of the article examines the evolution of these concepts in South Korean discourse. The circumstances of the formation and development of the military-political alliance with the United States play an extremely important role in this evolution, and the discourse around its prospects largely determines the features of the country’s domestic policy. The authors conclude that from the academic point of view the concept of “strategic autonomy” can only be considered as a discursive category close to the concept of “hedging,” but it is an important element of South Korea’s political identity and an essential factor of internal political struggle.